Bionic paw-inspired structure for vibration isolation with novel nonlinear compensation mechanism. (12th May 2022) - Yan, Ge; Qi, Wen-Hao; Shi, Jun-Wei; Yan, Han; Zou, Hong-Xiang; Zhao, Lin-Chuan; Wu, Zhi-Yuan; Fang, Xiao-Yong; Li, Xiu-Yuan; Zhang, Wen-Ming
Highlights: A unique and compact paw-inspired structure (PIS) is proposed and validated to imitate the compensation effect of fat pad on toes. QZS can be obtained by utilizing hardening stiffness to compensate the negative stiffness. The PIS provides a new low-frequency vibration isolation method with high application prospects. Abstract: Inspired by the compensation effect of fat pad on toes in a paw of digitigrade, a unique paw-inspired structure (PIS) is proposed and systematically investigated to explore its advantages in passive vibration isolation. The PIS consists of two key parts, one is the toe-like structure (TLS) simulated by two rods and a spring, and the other is fat pad mimicked by a pair of repulsive magnets. Based on the principle of virtual work, the static stiffness characteristics of the TLS are firstly analyzed. Then, the stiffness compensation mechanism of fat pad to toe is comprehensively studied. The hardening stiffness of the fat pad can compensate the negative stiffness of the TLS so that the PIS can realize quasi-zero stiffness (QZS) over large displacement range. It is for the first time to reveal this nonlinear stiffness compensation mechanism, which is essentially different from the conventional realization of QZS (connecting negative stiffness mechanism and linear spring in parallel). A dynamic model is established to estimate the vibration isolation performance. The displacement transmissibility derived by harmonic balance method (HBM) indicates that the PIS can achieve low resonance frequency and wide effective vibration isolation frequency band. Static tests are completed to verify effectiveness of the stiffness compensation mechanism. Tests under different external excitations (including periodic, sweep and random) show that the PIS can effectively suppress frequency components above 4 Hz. The PIS provides a new low-frequency vibration isolation method with high application prospects. And the proposed nonlinear stiffness mechanism can also be extended as a guideline to design nonlinear vibration isolators.